Subcritical Water Extraction of Phenolic Compounds from Mango Seed Kernel Using Response Surface Methodology - Yoswathana, Nuttawan; Eshiaghi, M.N. (Asian Journal of Chemistry, 2012)
Mango seed kernel, a waste generated from fruit processing, is a problem. But, the antioxidant property of phenolic compounds from mango seed kernel is a good source of functional ingredients. Optimization conditions for extracts yield and total phenolic content extraction from mango seed kernel by using subcritical water-ethanol extraction and conventional techniques such as maceration and soxhlet were investigated using response surface methodology. The studied factors of response surface methodology which influences the extraction yield were: temperature, extraction time and concentration of ethanol in water. The optimum conditions of extracts yield were obtained as follows: temperature at 130 ºC, extraction time for 40 min, concentration of 50 % ethanol. Under these conditions the maximum extracts yield was 71.83%. Subcritical water extraction of total phenolic content (using Folin-Ciocalteu's phenol reagent) was 40.4 mg of tannic acid equivalent per g dry mango seed kernel) much more than six times of that from conventional techniques. It is considered that the subcritical water extraction could be recommended as an alternative technique.